Biological activity and chemical composition of the essential oil from the fruits of Ferula rigidula Fisch. ex DC. - İşcan, Gökalp; Kürkçüoğlu, Mine; Tosun, Fatma; Miski, Mahmut (Istanbul Medipol University, 2023)
The hydro-distilled essential oils of the fruits of F. rigidula Fisch. ex DC. was analyzed by Gas Chromatography (GC) and Gas Chromatography/Mass Spectrometry (GC/MS) systems at the same time. Thirty-one compounds were characterized rep-resenting 98.2% of the essential oils. The main components of the oil were determined as a-pinene and camphene (24% and 20%, respectively). The anticandidal and antibacterial effects of the essential oil were determined by using partly modi-fied CLSI protocols M27-A2 and M7-A7, respectively. The essential oil of the dried fruits showed several inhibitory effects on the tested bacteria panel (MIC, 62.5 to 2000 µg/mL) and Candida species (MIC, 125 to 1000 µg/mL).
Keywords: Antibacterial; Anticandidal; Ferula Rigidula; Essential Oil; GCMS